Encyclopedia of Interfacial Chemistry [7 Volume Set] : Surface Science and Electrochemistry - Wandelt,Klaus [Ed.] (London : Elsevier, 2018)
Encyclopedia of Interfacial Chemistry: Surface Science and Electrochemistry, Seven Volume Set summarizes current, fundamental knowledge of interfacial chemistry, bringing readers the latest developments in the field. As the chemical and physical properties and processes at solid and liquid interfaces are the scientific basis of so many technologies which enhance our lives and create new opportunities, its important to highlight how these technologies enable the design and optimization of functional materials for heterogeneous and electro-catalysts in food production, pollution control, energy conversion and storage, medical applications requiring biocompatibility, drug delivery, and more. This book provides an interdisciplinary view that lies at the intersection of these fields.
Keywords: Surface chemistry -- Surfaces; Interfacial Chemistry; Electrochemistry